2015
DOI: 10.1177/2158244015614070
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in the Use of Maternal Health Care Services in Nigeria

Abstract: This article examines the socioeconomic inequalities in the use of antenatal care and medical assistance at delivery in Nigeria, using the multi-rounds of the cross-sectional Nigerian Demographic Health Survey conducted between 1990 and 2008. The analyses include only women aged 15 to 49 with at least one live birth in the past 3 years preceding the surveys date. The socioeconomic indicators selected were household wealth index and women's level of education. The results indicate that the use of antenatal care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 30 publications
15
45
0
Order By: Relevance
“…This applies to the use of reproductive health care services as well. While several studies have shown that better-off women have easier access to reproductive health care [5,[7][8][9], other studies have demonstrated that socio-demographic factors such as marital status, education, occupation, residence typology, attitude of health workers, and distance to health facility also contribute to the inequality in the use reproductive health care among women [9][10][11][12][13][14][15][16]. In addition, it is unclear to what extent these determinants explain the use of reproductive health care and contribute to the differences between the groups [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…This applies to the use of reproductive health care services as well. While several studies have shown that better-off women have easier access to reproductive health care [5,[7][8][9], other studies have demonstrated that socio-demographic factors such as marital status, education, occupation, residence typology, attitude of health workers, and distance to health facility also contribute to the inequality in the use reproductive health care among women [9][10][11][12][13][14][15][16]. In addition, it is unclear to what extent these determinants explain the use of reproductive health care and contribute to the differences between the groups [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with other studies (Amugsi et al, 2016), the findings of this current study have implications for maternal and child health because improved autonomy of women would result in improved household decision-making regarding major household purchases and improved nutritional status of members of the household. For a country like Nigeria where there has been no substantial improvement in the under-5 mortality index, improving the ability of women to take decisions on health and improving her social capital through her ability to take decisions to visit family members can increase maternal health service utilization (Grown et al, 2005;Ahmed et al, 2010;Obiyan and Kumar, 2015) and maternal under-5 mortality (Fantahun et al, 2007;Varkey et al, 2010). Summarily, the authors of this current study noticed that women's levels of participation in household decision-making varied significantly across the six geopolitical zones in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…2. The division of a sample into quintiles is a well-established research procedure, where observations, study objects, or other elements are divided into five groups according to a defined criterion (e.g., Baldwin & Sabourin, 2002;Bellone et al, 2008;Dempsey, 2013Dempsey, , 2014Fama & French, 2002;Klinedinst, 2016;Lazonick & Mazzucato, 2013;Obiyan & Kumar, 2015). I have implemented a similar analysis to study the behavior of the variable LOI in regard to the three hypotheses.…”
Section: Appendixmentioning
confidence: 99%